Developing a Fully Glycosylated Full-Length SARS-CoV‑2 Spike Protein Model in a Viral Membrane - Woo, Hyeonuk; Park, Sang-Jun; Choi, Yeol Kyo; Park, Taeyong; Tanveer, Maham; Cao, Yiwei; Kern, Nathan R; Lee, Jumin; Yeom, Min Sun; Croll, Tristan I; Seok, Chaok; Im, Wonpil (The journal of physical chemistry. B, 2020)
This technical study describes all-atom modeling and simulation of a fully glycosylated full-length SARS-CoV-2 spike (S) protein in a viral membrane. First, starting from PDB: 6VSB and 6VXX, full-length S protein structures were modeled using template-based modeling, de-novo protein structure prediction, and loop modeling techniques in GALAXY modeling suite. Then, using the recently determined most occupied glycoforms, 22 N-glycans and 1 O-glycan of each monomer were modeled using Glycan Reader & Modeler in CHARMM-GUI. These fully glycosylated full-length S protein model structures were assessed and further refined against the low-resolution data in their respective experimental maps using ISOLDE. We then used CHARMM-GUI Membrane Builder to place the S proteins in a viral membrane and performed all-atom molecular dynamics simulations. All structures are available in CHARMM-GUI COVID-19 Archive (http://www.charmm-gui.org/docs/archive/covid19) so that researchers can use these models to carry out innovative and novel modeling and simulation research for the prevention and treatment of COVID-19.